La teologia di Papa Francesco per l’oggi e il futuro della Chiesa. Prima parte: Compito e missione del teologo - Sinopoli, Concetta (Alpha omega, 2014)
The task of theology and the mission of theologians is to offer an explanation of the Gospel and, by listening to the spirit, to support the Magisterium in its attempt to fulfil its own task of providing answers, adapted to the needs of each generation, to the perennial questions about the meaning of human life, in the present and in the future, anticipating the expectations and the aspirations of humanity and offering solutions the dramatic situations it faces. Authentic theology presupposes faith, animated by charity; it is a search for personal holiness, service which is attentive to the sensus fidelium, understanding faith and the scientia Dei. After Vatican II many valid voices were raised and many aspects of reality appeared on the horizon and so the number of disciplines increased and there is a risk of fragmentation. Current Catholic theology needs unity in this multiplicity, reconnecting itself with the Source which lies at its origins. This is what characterises Pope Francis’ theology, as, renewing pastoral and spiritual forms, he has given an extraordinary impulse to theological reflection as such. In the first part some of the International Theological Commission’s documents are examined. Then, the characteristics specific to Catholic theology are used to identify and to interpret the innovative theological features of the Pope’s Magisterium.